PROTECTION OF CHILDREN'S RIGHTS IN DIVORCE PROCEEDINGS: A COMPARATIVE ANALYSIS OF VIETNAMESE AND FRENCH LAWS AND RECOMMENDATIONS - Huyen, Vu Thi Thanh; Huong, Vu Thi Lan; Nhu, Nguyen Thi To (Veredas do Direito, 2026)
This article examines the protection of children’s rights in divorce proceedings through a comparative analysis of Vietnamese and French law, focusing on key aspects such as the best interests of the child, the right to be heard, the maintenance of parent–child relationships, alimony obligations, and enforcement mechanisms. Using doctrinal and comparative methods, the study finds that although Vietnamese law incorporates core principles of the United Nations Convention on the Rights of the Child (UNCRC), its implementation remains fragmented and lacks institutional coherence, whereas French law provides a more flexible and effective framework supported by specialized judicial institutions and an interdisciplinary support system, enabling individualized decision-making and more effective enforcement. On this basis, the article argues that the primary challenge in Vietnam lies in the gap between legal design and practical implementation, and proposes several reforms, including clarifying the best interests principle through guidelines and case law, establishing mechanisms for independent representation of children, strengthening support for the right to be heard, improving enforcement of maintenance obligations through data integration, and developing an interdisciplinary judicial support framework.